The Anti-Angiogenic Effect of Cynara cardunculus L. subsp. cardunculus Waste Product - Anna Cacciola; Valeria D’Angelo; Federica De Gaetano; Antonella Fais; Maria Paola Germanò; Valentina Masala; Stefania Olla; Venerando Pistarà; Rosanna Stancanelli; Carlo Ignazio Giovanni Tuberoso; Cinzia Anna Ventura (Foods)
Cynara cardunculus L. subsp. cardunculus (Cynara cardunculus L. var. sylvestris (Lam.) Fiori), the wild cardoon, is known for its culinary applications and potential health benefits. Due to this, and given the growing interest in circular economies, deepening our under-standing of the effects of wild cardoon leaf waste on angiogenesis and collagenase activity represents a valuable opportunity to valorise agricultural byproducts as health-promoting ingredients. In this study, the waste product of wild cardoon leaves was extracted to examine its chemical composition and biological activities. Analytical techniques identified several bioactive compounds, including flavonoids, hydroxycinnamic acids such as dicaffeoyl-succinoylquinic acids, and luteolin-7-O-rutinoside. In vivo tests in zebrafish embryos and the chick chorioallantoic membrane demonstrated dose-dependent antiangiogenic effects, particularly enhanced by the complexation with hydroxypropyl-β-cyclodextrin (HP-β-CD). Considering the link between angiogenesis and collagenase, the potential effects of the extract on collagenase activity was investigated. The extract alone inhibited collagenase with an IC50 value comparable to that of the standard inhibitor while its complexed form exhibited a 4.5-fold greater inhibitory activity. A molecular docking study examined the interaction between the main compounds and collagenase. In conclusion, wild cardoon leaves can represent a valuable source of bioactive compounds. This study demonstrated that the complexation of the extract with cyclodextrin determines an increase in its biological activity.